An Implementation of the Matrix Multiplication Algorithm SUMMA in mpF - Kalinov, Alexey; Ledovskikh, Ilya; Posypkin, Mikhail; Levchenko, Zakhar; Chizhov, Vladimir (Parallel Computing Technologies, 2005)
In this paper, we present a new parallel Fortran extension called mpF. The language based on both data and task parallelism allows explicit specification of data and computations distribution. We discuss some reasons for the language design and demonstrate the basic mpF features on an example of the parallel matrix multiplication algorithm SUMMA. The mpF implementation is compared with its MPI counterpart.